Multi-experiment state-space identification of coupled magnetic and kinetic parameters in tokamak plasmas. (March 2017) - Mavkov, B.; Witrant, E.; Prieur, C.; Moreau, D.
Abstract: This paper describes an identification technique for control-oriented linear time-invariant models of the coupled dynamics of the electron temperature and the poloidal magnetic flux for advanced operational tokamak scenarios. The actuators consist of two neutral beam injectors, an electron cyclotron current drive and the ohmic coil that provides the loop voltage at the plasma surface. The model is identified using a combination of subspace and output-error methods for state-space multiple-input and multiple-output system identification. This identification is applied on sets of simulated data from the METIS tokamak simulator with parameters typical of the DIII-D tokamak, and the results of the identification are presented.